Factors increasing the risk of mortality and morbidity due to coronavirus infection in patients with metabolic syndrome - Altansuvd Enkhtur; Joon-Sup Yoon; Chang-Woo Lee (Precision and Future Medicine, 2020)
Patients living with comorbid metabolic syndrome (MS) and metabolic disorders such as obesity and type 2 diabetes mellitus carry increased levels of circulating cytokines and systemic low-grade inflammation. Upon viral infection, such patients with all pre-existing backgrounds, specifically dysregulated inflammatory signalling, leads to rapid viral replication and results in worse clinical outcomes. The increased pro-inflammatory cytokine release is a risk factor, and therefore, targeting inflammatory signalling pathways represents a potential therapeutic target to control the cytokine release, and thereby prevent serious outcomes, such as increased mortality and morbidity. In this review, we elucidate the factors underlying the increased morbidity and mortality in patients with MS and virus infection, particularly coronavirus.